YOUNG CONSUMERS’ ATTITUDES TOWARD CELEBRITY ENDORSERS IN ADVERTISING - Nuri Paşa Özer; A. Mücahid Zengin (Selçuk İletişim)
Using celebrities as brand endorsers may seem like a simple shortcut for an effective advertising. Celebrities are attention grabbing and they possess many meanings that they can transfer to brands. However, there are several risks in using celebrities, such as overshadowing the brand, scandals that the celebrity might get involved, and the possibility of conflicting meanings that the celebrity might bring. This study focuses on the first three commercials by Rexona starring Orhan Gencebay. A survey was conducted on 280 university students to reveal attitudes toward the brand and the commercials, perceived match-up between the brand and celebrity, in addition to the perceived attractiveness, trustworthiness and expertise of Orhan Gencebay. The findings suggest that the participants like the Rexona brand more than the commercials, and they do not perceive the brand and the endorser as a fit. The meanings that Orhan Gencebay bears according to the participants were also explored. The word “arabesque” is followed by words about sadness. The results of this study suggest that brands should take celebrity-product match-up into account when selecting an endorser and not be contented with the endorser’s attention grabbing power.